This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 1. For both of the following, assume that A,B R and that neither are empty. (a) (10pts) Show that A B = sup A sup B . Solution. If B is not bounded above, then sup B = , and it is trivial. So let b := sup B < and a := sup A . Then b is an upper bound for B , so x A B implies x b , and hence b is an upper bound for A . Then a b by definition of a as a supremum. (b) (10pts) Show that sup( A B ) = max { sup A, sup B } . Solution. Show both inequalities. x A = x sup A = x { sup A, sup B } . Similarly, x B = x { sup A, sup B } . Since we have shown the inequality in either case, we have x ( A B ) , x max { sup A, sup B } = sup( A B ) max { sup A, sup B } , since max { sup A, sup B } is an upper bound for A B . A A B = sup A sup( A B ) by the first part. The same argument shows sup B sup( A B ). Therefore, the inequality holds for whichever is larger, i.e., max { sup A, sup B } sup( A B ). 2. (20pts) Let s 1 = 2 and s n +1 = p 2 + s n . Prove { s n } converges. If you use the fact that a < b a < b ( a,b > 0), please attach a copy of this proof. (Hint: show0), please attach a copy of this proof....
View Full
Document
 Spring '06
 Spielberg

Click to edit the document details